ACCURACY OF RAPID TEST OF STORED ACUTE PHASE SERUM FOR DIAGNOSE JAPANESE ENCEPHALITIS - Subanada, Ida Bagus; Kari, I Komang (Medicina; Vol 44 No 1 (2013): Januari 2013, 2013)
Normal 0 false false false IN X-NONE X-NONE Japanese encephalitis (JE) is common viral encephalitis with high sequele and mortality. With some limitations, there are several diagnostic tool to diagnose of JE. The objecive of t his study was to know the accuracy of rapid test of stored acute phase serum for diagnose of JE . We conducted diagnostic test of stored acute phase serum of encephalitis patients with MAC ELISA of cerebrospinal fluid as a gold standard. S ensitivity, specificity, positive predictive value (PPV), negative predictive value NPV), positive likelihood ratio (PLR), negative likelihood ratio (NLR), and post-test probability were calculated . This study found the prevalence of JE was 42.1%, sensitivity 15.7 % (95% CI 9.2 to 22.2%), specificity 95.7% (95% CI 92.1 to 99.3%), PPV 72.7% (95% CI 64.8 to 80.6%), NPV 60.9% (95% CI 52.2 to 69.6%), PLR 3.7, NLR 0.9, and post-test probability was 0.73. We concluded that rapid test of acute phase stored serum was insensitive but specific to diagnose of JE. /* Style Definitions */ table.MsoNormalTable {mso-style-name:"Table Normal"; mso-tstyle-rowband-size:0; mso-tstyle-colband-size:0; mso-style-noshow:yes; mso-style-priority:99; mso-style-qformat:yes; mso-style-parent:""; mso-padding-alt:0cm 5.4pt 0cm 5.4pt; mso-para-margin:0cm; mso-para-margin-bottom:.0001pt; mso-pagination:widow-orphan; font-size:11.0pt; font-family:"Calibri","sans-serif"; mso-ascii-font-family:Calibri; mso-ascii-theme-font:minor-latin; mso-fareast-font-family:"Times New Roman"; mso-fareast-theme-font:minor-fareast; mso-hansi-font-family:Calibri; mso-hansi-theme-font:minor-latin; mso-bidi-font-family:"Times New Roman"; mso-bidi-theme-font:minor-bidi;}
Keywords: acute phase stored serum, rapid test, accuracy